Theoretical prediction of high melting temperature for a Mo–Ru–Ta–W HCP multiprincipal element alloy - Qi-Jun Hong (npj Computational Materials, 2021)
Abstract While rhenium is an ideal material for rapid thermal cycling applications under high temperatures, such as rocket engine nozzles, its high cost limits its widespread use and prompts an exploration of viable cost-effective substitutes. In prior work, we identified a promising pool of candidate substitute alloys consisting of Mo, Ru, Ta, and W. In this work we demonstrate, based on density functional theory melting temperature calculations, that one of the candidates, Mo0.292Ru0.555Ta0.031W0.122, exhibits a high melting temperature (around 2626 K), thus supporting its use in high-temperature applications.